HMG Box Transcriptional Repressor HBP1 Maintains a Proliferation Barrier in Differentiated Liver Tissue - Shih, Heather H. (American Society for Microbiology, 2001)
We previously isolated HBP1 as a target of the retinoblastoma (RB) and p130 family members and as the first of the HMG box transcriptional repressors. Our subsequent work demonstrated that HBP1 coordinates differentiation in cell culture models. In the present study, we show that HBP1 regulates proliferation in a differentiated tissue of an animal. Using transgenic mice in which HBP1 expression was specifically increased in hepatocytes under control of the transthyretin promoter, we determined the impact of HBP1 on synchronous cell cycle reentry following partial hepatectomy. Modest overexpression of HBP1 yielded a detectable cell cycle phenotype. Following a mitogenic stimulus induced by two-thirds partial hepatectomy, mice expressing the HBP1 transgene showed a 10- to 12-h delay in progression through G(1) to the peak of S phase. There was a concomitant delay in mid-G(1) events, such as the induction of cyclin E. While the delay in G(1) and S phases correlated with the slight overexpression of transgenic HBP1, the level of the endogenous HBP1 protein itself declined in S phase. In contrast, the onset of the immediate-early response following partial hepatectomy was unchanged in HBP1 transgenic mice. This observation indicated that the observed delay in S phase did not result from changes in signaling pathways leading into the G(0)-to-G(1) transition. Finally, transgenic mice expressing a mutant HBP1 lacking the N-terminal RB interacting domain showed a stronger S-phase response following partial hepatectomy. These results provide the first evidence that HBP1 can regulate cell cycle progression in differentiated tissues.